Quality of Life Among Patients With Chronic Kidney Disease Who are Undergoing Haemodialysis at Two Selected Teaching Hospitals in Sri Lanka - M.A.S.S. Premadasa; H.G.I.M. Hulangamuwa; W.A.D.H. Wijesooriya; T.D. Amarasekara (The Open University of Sri Lanka, 2019)
Chronic Kidney Disease (CKD) has shown a rising trend in Sri Lanka. Haemodialysis (HD) is a method of managing patients with CKD. Improving and maintaining Quality of Life (QOL) is an essential goal of nursing care for patients with CKD. However, there is a paucity of data on QOL among patients with CKD who are undergoing HD in Sri Lanka. Therefore, this study aimed at assessing the QOL among patients with CKD who are undergoing HD at haemodialysis units in selected teaching hospitals in Sri Lanka. A descriptive cross-sectional study was conducted with purposively selected participants (n=250) at haemodialysis units in the above settings. Data was obtained through two pre-tested questionnaires, Socio-demographic questionnaire and WHOQOLBREF, and they were analysed using descriptive statistics. Ethical approval was obtained from the ethics review committee, KAATSU International University (KIU), Sri Lanka. Findings revealed that the majority of participants were male 184 (73.6%), and belonged to the 30-64 age group. Nearly half of them (48.4%) have undergone HD treatment for periods ranging from 3 months to1 year duration, and 54% of them have been admitted three times per week for HD. Data revealed that the Environmental domain has the highest mean value (59.2±16.6), and social relationship domain has the least (49.5±22.5). Physical health and psychological domains were 51.9 (15.6), and 52.3 (19.9) mean values, respectively. Most of the participants (69.2%) were observed having poor overall QOL. Statistically, significant p values were as follows: Participants' education level (p=0.000), average monthly income (p=0.002) and the frequency of dialysis towards QOL (p=0.000). Health education programs should be organised to enhance QOL among patients with CKD and undergoing HD.